TGF-β Small Molecule Inhibitor SB431542 Reduces Rotator Cuff Muscle Fibrosis and Fatty Infiltration By Promoting Fibro/Adipogenic Progenitor Apoptosis. - Michael R Davies; Xuhui Liu; Lawrence Lee; Dominique Laron; Anne Y Ning; Hubert T Kim; Brian T Feeley (PLoS ONE)
Rotator cuff tears represent a large burden of muscle-tendon injuries in our aging population. While small tears can be repaired surgically with good outcomes, critical size tears are marked by muscle atrophy, fibrosis, and fatty infiltration, which can lead to failed repair, frequent re-injury, and chronic disability. Previous animal studies have indicated that Transforming Growth Factor-β (TGF-β) signaling may play an important role in the development of these muscle pathologies after injury. Here, we demonstrated that inhibition of TGF-β1 signaling with the small molecule inhibitor SB431542 in a mouse model of massive rotator cuff tear results in decreased fibrosis, fatty infiltration, and muscle weight loss. These observed phenotypic changes were accompanied by decreased fibrotic, adipogenic, and atrophy-related gene expression in the injured muscle of mice treated with SB431542. We further demonstrated that treatment with SB431542 reduces the number of fibro/adipogenic progenitor (FAP) cells-an important cellular origin of rotator cuff muscle fibrosis and fatty infiltration, in injured muscle by promoting apoptosis of FAPs. Together, these data indicate that the TGF-β pathway is a critical regulator of the degenerative muscle changes seen after massive rotator cuff tears. TGF-β promotes rotator cuff muscle fibrosis and fatty infiltration by preventing FAP apoptosis. TGF-β regulated FAP apoptosis may serve as an important target pathway in the future development of novel therapeutics to improve muscle outcomes following rotator cuff tear.